Geodetic modelling of the 2022 Mw 6.6 Menyuan earthquake: insight into the strain-partitioned northern Qilian Shan fault system and implications for regional tectonics and seismic hazards. Issue 3 (17th January 2023) - Zhang, Yingfeng; Chen, Jie; Gong, Wenyu; Han, Nana; Liu, Yunhua; Shan, Xinjian
SUMMARY: Strain partitioning between strike-slip faults in mountains and thrust faults in the foreland is a typical mountain building process to accommodate oblique plate convergence. Studying the geometry and movement of such strain-partitioned fault systems is key to understanding the mountain building process and related seismic hazards. The 2022 M w 6.6 Menyuan earthquake is the largest strike-slip earthquake to have ruptured the northern Qilian Shan fault system in the modern geodetic era. We combined satellite and field observations to determine the fault geometry and coseismic slip distribution in the Menyuan earthquake, and link the distribution of coseismic slip with the pattern of interseismic strain accumulation within the northern Qilian Shan from our geodetic slip model. We find that the Menyuan earthquake ruptured a 25 km-long section of the left-lateral Longlongling Fault between the surface and 7 km depth. The maximum slip was 4 m at 3–4 km depth. Damage to a high-speed railway tunnel recorded a fault offset of 2.7 m at a depth of 200 m compared to 2.5–3.0 m on the surface, suggesting that dispersion of the rupture through unconsolidated shallow sediments was limited, at least at the tunnel site. We also determined the pattern of interseismic deformation prior to the earthquake using Interferometric Synthetic Aperture Radar and Global Navigation Satellite System data. We found the interseismic geodetic data can be explained by the oblique movement of a low-angle décollement beneath the Qilian Shan rather than a strain partitioning fault system. We suggested that the strike-slip faults and foreland thrusts are separated by a creeping décollement, which would act as a barrier to stop the cascading rupture of the strike-slip and thrust fault.